The success rate formation as the foundation for the growth of students’ personalities in contemporary circumstances (Revista de Investigaciones Universidad del Quindío, 2022)
This current study is focused on the quest for procedures for the success rate formation as the foundation for the harmonious growth of the students’ personalities in contemporary circumstances. The new generation of “Pepsi” is indifferent and not resilient in a substantial part. This article carried out an analysis of the recent practical and scientific and empirical research on a case of 9 grade students.  The authors have chosen methods and tools to obtain data in the shape of techniques of investigating of the outcomes of educational tasks, observation, surveys, and conversations and utilized the poorly formalized “unfinished sentences” method to investigate the adolescents’ educational success. The result of the diagnostic cross-section to determine the success rate and its indicators is reflected. Also in this paper, the results of interviews on the subject of social assessments of successful personalities of adolescents are presented.
Keywords: Success rate; Active life position; Harmonious development; Self-assessment; Social apathy